Characterizing Endocrine Status, Tumor Hypoxia and Immunogenicity for Therapy Success in Epithelial Ovarian Cancer - Pereira, Madison; Matuszewska, Kathy; Jamieson, Colin; Petrik, Jim (Frontiers in Endocrinology, 2021)
Epithelial ovarian cancer is predominantly diagnosed at advanced stages which creates significant therapeutic challenges. As a result, the 5-year survival rate is low. Within ovarian cancer, significant tumor heterogeneity exists, and the tumor microenvironment is diverse. Tumor heterogeneity leads to diversity in therapy response within the tumor, which can lead to resistance or recurrence. Advancements in therapy development and tumor profiling have initiated a shift from a “one-size-fits-all” approach towards precision patient-based therapies. Here, we review aspects of ovarian tumor heterogeneity that facilitate tumorigenesis and contribute to treatment failure. These tumor characteristics should be considered when designing novel therapies or characterizing mechanisms of treatment resistance. Individual patients vary considerably in terms of age, fertility and contraceptive use which innately affects the endocrine milieu in the ovary. Similarly, individual tumors differ significantly in their immune profile, which can impact the efficacy of immunotherapies. Tumor size, presence of malignant ascites and vascular density further alters the tumor microenvironment, creating areas of significant hypoxia that is notorious for increasing tumorigenesis, resistance to standard of care therapies and promoting stemness and metastases. We further expand on strategies aimed at improving oxygenation status in tumors to dampen downstream effects of hypoxia and set the stage for better response to therapy.